2019
DOI: 10.1080/17538947.2019.1651912
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of global crop water productivity of three leading world crops (wheat, corn, and rice) in the irrigated areas over three decades

Abstract: The overarching goal of this study was to perform a comprehensive metaanalysis of irrigated agricultural Crop Water Productivity (CWP) of the world's three leading crops: wheat, corn, and rice based on three decades of remote sensing and non-remote sensing-based studies. Overall, CWP data from 148 crop growing study sites (60 wheat, 43 corn, and 45 rice) spread across the world were gathered from published articles spanning 31 different countries. There was overwhelming evidence of a significant increase in CW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 123 publications
2
20
0
Order By: Relevance
“…Preceding studies showed that maize yield is a linear function of seasonal evapotranspiration (Gilley et al, 1980;Payero et al, 2006;Klocke et al, 2004;Stone, 2003). Also, the linear relationship between relative crop yield (Ya/Ym) and relative maize evapotranspiration (ETa/ETm) as the following relation developed by Doorenbos and Kassam (1979) for the first time.…”
Section: Maize Yield and Evapotranspiration Relationmentioning
confidence: 99%
See 4 more Smart Citations
“…Preceding studies showed that maize yield is a linear function of seasonal evapotranspiration (Gilley et al, 1980;Payero et al, 2006;Klocke et al, 2004;Stone, 2003). Also, the linear relationship between relative crop yield (Ya/Ym) and relative maize evapotranspiration (ETa/ETm) as the following relation developed by Doorenbos and Kassam (1979) for the first time.…”
Section: Maize Yield and Evapotranspiration Relationmentioning
confidence: 99%
“…Deficit irrigation method is one of the common strategies for producing crops under water deficit and limitation conditions in the arid and semi-arid environments over of the world. Deficit irrigation efficiency in crop production is evaluated by an index known as water productivity (WP) that is crop yield from applying 1 m 3 of irrigation water (Foley et al, 2020;Katerji et al, 2013). This index was considerably applied in crop irrigation researches in irrigated farms (Abadi et al, 2010;Bramley et al, 2013;Du et al, 2010;Fang et al, 2010;Guo et al, 2010;Li et al, 2010;Zhang et al, 2010;Nasseri and Bahramloo, 2009;Nasseri and Fallahi, 2007;Zamani and Nasseri, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations